Use of visual range measurements to predict fine particulate matter exposures in Southwest Asia and Afghanistan. (2nd January 2017) - Masri, Shahir; Garshick, Eric; Hart, Jaime; Bouhamra, Walid; Koutrakis, Petros
ABSTRACT: Military personnel deployed to Southwest Asia and Afghanistan were exposed to high levels of ambient particulate matter (PM). However, quantitative ambient exposure data for conducting health studies are limited due to a lack of PM monitoring stations. Since visual range (VR) is proportional to particle light extinction, VR can serve as a surrogate for PM2.5 (particulate matter with an aerodynamic diameter ≤2.5 µm) concentrations. We used data on VR, relative humidity (RH), and PM2.5 ground measurements collected in Kuwait from years 2004–2005 to establish the relationship between PM2.5 and VR. Model validation obtained by regressing trimester average PM2.5 predictions against PM2.5 measurements in Kuwait produced an r 2 value of 0.84. Cross validation of urban and rural sites in Kuwait also revealed good model fit. We applied this relationship to location-specific visibility data at 104 regional sites between years 2000-2012 to estimate monthly average PM2.5 concentrations. Monthly averages at sites in Iraq, Afghanistan, United Arab Emirates, Kuwait, Djibouti, and Qatar ranged from 10 to 365 µg/m3 during this period, while site averages ranged from 22 to 80 µg/m3, indicating considerable spatial and temporal heterogeneity in ambient PM2.5 across these regions. These data support the use of historical visibility data to estimate location-specific PM2.5 concentrations for application in epidemiological studies. Implications : This study demonstrates the ability to use airport visibility to estimate PM2.5 concentrations in Southwest Asian and Afghanistan. This supports the use of historical and ongoing visibility data to estimate PM2.5 exposure in this region of the world, where PM exposure information is otherwise scarce. This is of high utility to epidemiologists investigating the relationship between chronic exposure to PM2.5 and respiratory diseases among deployed military personnel stationed at various military bases throughout the region. Such information will enable the drafting of improved policies relating to military health.